Financiamento público e privado de campanhas eleitorais: efeitos sobre bem-estar social e representação partidária no Legislativo - Portugal, Adriana Cuoco; Bugarin, Mauncio (Economia Aplicada, 2003)
This article analyzes the effect of public electoral financing on parties' announced policies and the distribution of parties in the Legislature. Electoral campaign may be financed by public funds from the government and private contributions from interest groups. When only private contributions are available, the winning policy is biased towards the strongest interest groups' ideal point, but the representation of parties in Congress results in a balanced Legislature. When only public financing is allowed the winning policy is socially optimal, and one party may become preponderant in the Legislature. Finally, if both private and public campaign financing are available then, the winning policy is suboptimal, and one party may become dominantin the long run. Therefore, a campaign financing reform may lead to antagonistic results depending on the role of private contributions and the size of public funds.